The chair: a form of organization of the university teaching function (Praxis Educativa, 2020)
Institutions aimed to a social function fulfillment. To do this the institutions are specified in an organization, with its space, its time and through a distribution of responsibilities and tasks. In Argentine history and tradition, teaching as a function is usually assigned to the university chair. Chairs are generally named after the subject or knowledge field that is taught, which highlights the importance of this function. Although this article falls within the results of our research on the teaching styles of the university chair, this form of organization was already presented as a relevant notion in our previous studies located in the fieldof university didactics. The objectives of this work are to analyze the senses and meanings attributed to the university chair, as well as to present the institutional and pedagogical – teaching aspects that constitute it.
Keywords: university chair; university education; college; university organization.